Dietary Inflammatory Index and Health Outcomes: An Umbrella Review of Systematic Review and Meta-Analyses of Observational Studies - Liu, Fang-Hua; Liu, Chuan; Gong, Ting-Ting; Gao, Song; Sun, Hui; Jiang, Yu-Ting; Zhang, Jia-Yu; Zhang, Meng; Gao, Chang; Li, Xin-Yu; Zhao, Yu-Hong; Wu, Qi-Jun (Frontiers in Nutrition, 2021)
Background & Aims: Dietary inflammatory index (DII) is related to non-communicable disease. We conducted the umbrella review to systematically evaluate the meta-analyses of observational studies on DII and diverse health outcomes. Methods: We comprehensively searched PubMed, Web of Science, Embase databases to identify related systematic reviews and meta-analyses of observational studies. Systematic reviews with meta-analyses of observational studies that investigated the association between DII and a wide range of health outcomes in humans are eligible. For each meta-analysis, we estimated the summary effect size using fixed and random effects models, the 95% confidence interval and the 95% prediction interval. We assessed heterogeneity, evidence of small- study effects, and excess significance bias. Results: The umbrella review identified 35 meta-analyses that assessed associations between DII and various health outcomes, which related to cancer outcomes (n=24), mortality (n=4), metabolic outcomes (n=4) and other outcomes (n=3). Methodological quality was high or medium. Of the 35 meta-analyses, we observed highly suggestive evidence for harmful associations between digestive tract cancer, colorectal cancer, overall cancer, pharynx cancer, UADT cancer, and CVD mortality. Moreover, 11 harmful associations showed suggestive evidence, including hormone-dependent cancer, rectal cancer, colon cancer, breast and prostate cancer, gynecological cancer, breast cancer, ovarian cancer, colorectal cancer, prostate cancer, all-cause mortality, depression. Conclusion: DII is more likely associated with harmful effects for multiple health outcomes. Robust randomized controlled trials are warranted to understand whether the observed results are causal.